Computational Thinking and the Circulatory System - Aytekin, Aydan; Topcu, Mustafa sami (NATL ASSOC BIOLOGY TEACHERS INC, 2025)
The circulatory system is one of the complicated science subjects that science teachers must teach, presenting substantial conceptual learning challenges for students. Therefore, the aim of this study was to facilitate the teaching and learning of the circulatory system in a more concrete and understandable way. To achieve this, the study integrated computational thinking (CT) elements into science teaching and developed an unplugged circulatory system teaching module centered on CT principles. The unplugged CT approach, involves students recognizing CT elements in student-centered learning environments without computers through various tangible materials (paper, colored pencils, scissors, glue, colored cartons, puzzle pieces, stickers, etc.), various games, physical activities, competitions, kinesthetic activities, and more. In this student-centered learning environment the teacher guides students when they encounter difficulties in engaging and learning through unplugged CT activities. The unplugged teaching module consists of 10 different activities (4 activities shared due to space limitation) and lasts 4 weeks (16 lesson hours). As a result, thanks to the developed teaching module, students learned the concepts of the circulatory system more concretely and in a more organized way, showing how computational thinking elements are integrated into the subject through these activities.
Keywords: computational thinking; circulatory sys- tem; unplugged computational thinking approach; Life Sciences & Biomedicine - Other Topics; Education & Educational Research